2012
DOI: 10.3354/esr00427
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in marine mammal habitat modelling: evidence of multiple foraging habitats from the identification of feeding events in blue whales

Abstract: Effective conservation of animal species depends on accurate identification of their critical habitat. Marine mammals, however, often transit through heterogeneous habitats and perform various activities within short periods of time. The predictive power of habitat modelling techniques can thus suffer from variability in behaviour and the use of multiple habitat types. We used data loggers and ecological-niche factor analysis (ENFA) modelling techniques to determine blue whale Balaenoptera musculus association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…This was illustrated by a study using a blue whale presenceonly habitat model, which identified topographical heterogeneity as an important variable explaining foraging blue whale distribution in the SLE. Blue whales exploited slope areas, as well as plateaus and deep areas over flat beds as feeding habitat at certain periods of the tidal cycle (Doniol-Valcroze et al 2012). In general, there was strong agreement between areas we identified based on blue whale ARS behaviour (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…This was illustrated by a study using a blue whale presenceonly habitat model, which identified topographical heterogeneity as an important variable explaining foraging blue whale distribution in the SLE. Blue whales exploited slope areas, as well as plateaus and deep areas over flat beds as feeding habitat at certain periods of the tidal cycle (Doniol-Valcroze et al 2012). In general, there was strong agreement between areas we identified based on blue whale ARS behaviour (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…Even when shifts in shipping lanes are used, they may result in a reduction, but not elimination, of the risk of ship−whale encounters as whale aggregations may shift within and among years with shifts in prey or oceanographic conditions (e.g. Witteveen et al 2008, Chenoweth et al 2011, Becker et al 2012, Doniol-Valcroze et al 2012, Heide-Jørgensen et al 2012, Keller et al 2012, Pendleton et al 2012, Gregr et al 2013.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…Using the data available on marine mammal abundance, distribution, diet composition and foraging strategies, spatial models can be applied to project the range of a foraging habitat and, thus, estimate the potential of spatial, temporal and resource overlap (see Doniol-Valcroze et al 2012).…”
Section: Using Sea Otters As An Example) For Instance Femalementioning
confidence: 99%